Inverse electron demand DielsAlder (iEDDA)-initiated conjugation: a (high) potential click chemistry scheme - Knall, Astrid-Caroline; Slugovc, Christian (2013)
Inverse electron demand DielsAlder reactions (iEDDA) between 1,2,4,5-tetrazines and olefins have emerged into a state-of-the art concept for the conjugation of biomolecules. Now, this reaction is also increasingly being applied in polymer science and materials science. The orthogonality of this exciting reaction to other well-established click chemistry schemes, its high reaction speed and its biocompatibility are key features of iEDDA making it a powerful alternative to existing ligation chemistries. The intention of this tutorial review is to introduce the reader to the fundamentals of inverse electron demand DielsAlder additions and to answer the question whether iEDDA chemistry is living up to the criteria for a click reaction and can serve as a basis for future applications in post-synthetic modification of materials. Inverse electron demand DielsAlder reactions (iEDDA) between 1,2,4,5-tetrazines and olefins have emerged as a versatile conjugation tool in the sense of click chemistry and are therefore the subject of this tutorial review .